Enrichment of human nasopharyngeal bacteriome with bacteria from dust after short-term exposure to indoor environment: a pilot study - Konecna, Eva; Videnska, Petra; Buresova, Lucie; Urik, Milan; Smetanova, Sona; Smatana, Stanislav; Prokes, Roman; Lanickova, Barbara; Budinska, Eva; Klanova, Jana; Borilova Linhartova, Petra (BMC microbiology, 2023)
BACKGROUND: Indoor dust particles are an everyday source of human exposure to microorganisms and their inhalation may directly affect the microbiota of the respiratory tract. We aimed to characterize the changes in human nasopharyngeal bacteriome after short-term exposure to indoor (workplace) environments. METHODS: In this pilot study, nasopharyngeal swabs were taken from 22 participants in the morning and after 8 h of their presence at the workplace. At the same time points, indoor dust samples were collected from the participants' households (16 from flats and 6 from houses) and workplaces (8 from a maternity hospital - NEO, 6 from a pediatric hospital - ENT, and 8 from a research center - RCX). 16S rRNA sequencing analysis was performed on these human and environmental matrices. RESULTS: Staphylococcus and Corynebacterium were the most abundant genera in both indoor dust and nasopharyngeal samples. The analysis indicated lower bacterial diversity in indoor dust samples from flats compared to houses, NEO, ENT, and RCX (p < 0.05). Participants working in the NEO had the highest nasopharyngeal bacterial diversity of all groups (p < 0.05). After 8 h of exposure to the workplace environment, enrichment of the nasopharynx with several new bacterial genera present in the indoor dust was observed in 76% of study participants; however, no significant changes were observed at the level of the nasopharyngeal bacterial diversity (p > 0.05, Shannon index). These "enriching" bacterial genera overlapped between the hospital workplaces - NEO and ENT but differed from those in the research center - RCX. CONCLUSIONS: The results suggest that although the composition of nasopharyngeal bacteriome is relatively stable during the day. Short-term exposure to the indoor environment can result in the enrichment of the nasopharynx with bacterial DNA from indoor dust; the bacterial composition, however, varies by the indoor workplace environment.
Keywords: Air Pollution, Indoor; Hospital; Indoor environment; Female; dítě; ženské pohlaví; nazofarynx; RNA, Ribosomal, 16S; 16S rRNA; lidé; Pilot Projects; těhotenství; pilotní projekty; Nasopharynx; Exposure; Bacteriome; znečištění vzduchu ve vnitřním prostředí; Sequencing; prach; Bacteria; Dust; Household; Child; Pregnancy; RNA ribozomální 16S; Humans